Effect of Isothermal Heat Treatment on Cyclic Life of Yitria Stabilized Zirconia and Gadolinium Zirconate Thermal Barrier Coating - Johari A.D.; Yunus S.M.; Biyamin S.A.; Rahman M.M.; Hasini H.; Manap A. (Elsevier Ltd, 2023)
Aluminum alloys; Chromium alloys; Gadolinium; Heat treatment; Isotherms; Plasma spraying; Thermal barrier coatings; Yttrium oxide; Cyclic lives; Five-layered; Functionally graded; Gadolinium zirconate; Isothermal heat treatments; NiCrAlY; Stabilized zirconia; Thermal; Thermal exposure; Yttria-stabilized-zirconia; Yttria stabilized zirconia